IMPROVISATION, INTUITION E INSTANT (Olhares, 2025)
In this reflection, I propose to weigh the fertile moment, a creative instant of improvisation, a fundamental experience for the performer. This thought about practice was built from my own experiences as an actor, although always under collective laboratories experiences, powerful path to scenic creation. Inspired by the book “The intuition of the instant” by the French philosopher Gaston Bachelard, in dialogue with the researches of the performing arts Constantin Stanislavski e Eugenio Kusnet, among others, and first pointed out in the doctoral research, it has its first steps in investigations carried out based on the scene creations of “Boa Companhia”, a theatrical research group that’s I had work since in 1992 and lasted until 2017.
Keywords: improvisation; scenic composition; active analysis; Bachelard; intuition and instant